Schools of Thought in Social Entrepreneurship - Bravo Monge, Cris (2016)
Social Entrepreneurship is a new and exciting topic that holds a great promise in helping alleviate the social problems in the world. As a new subject, the meaning of the term is too broad which interferes with the construction and understanding of the concept. The purpose of this study is to identify the elements of the different proposals of what social entrepreneurship looks like, from the perspective of four organizations leading social entrepreneurship projects: Ashoka Foundation, Skoll Foundation, Schwab Foundation and Yunus Center; as well as from three other field and academic related institutions fostering and practicing social entrepreneurship. The study used document analysis from Skoll Foundation, Schwab Foundation, Yunus Center and Ashoka Foundation, and an open ended interview applied to experts from practitioner institutions. The study identified three clearly differentiated schools of thought, based on their views on revenue, scalability, replicability and geographic location. The definition of the different schools of thoughts is particularly important for the teaching of social entrepreneurship, and for the promotion of more adequate and accurate social policies to foster the development of social entrepreneurship.